2003
DOI: 10.1038/sj.onc.1206378
|View full text |Cite
|
Sign up to set email alerts
|

MAL gene expression in esophageal cancer suppresses motility, invasion and tumorigenicity and enhances apoptosis through the Fas pathway

Abstract: We isolated the MAL (T-lymphocyte maturation associated protein) gene from differentially expressed products of esophageal epithelium relative to esophageal carcinoma tissues. The Mal protein has been demonstrated as being a component of the protein machinery for apical transport in epithelial polarized cells. In this study, we describe the reduced expression of MAL in all 39 cases of esophageal carcinoma tested and 60 other human carcinomas. MAL gene transcription was induced in three out of 13 esophageal car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
80
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 27 publications
5
80
0
Order By: Relevance
“…They are involved in a variety of biological processes, including cell cycle progression, chemotactic activity, tight junction, and clathrin-mediated endocytosis. (15,(18)(19)(20) It is documented that MARVEL domain-containing proteins are decreased in various types of cancer, and exert tumor-suppressive functions. (12)(13)(14)(15) MARVELD1 is a novel member of this family, with very limited work performed so far about its molecular function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are involved in a variety of biological processes, including cell cycle progression, chemotactic activity, tight junction, and clathrin-mediated endocytosis. (15,(18)(19)(20) It is documented that MARVEL domain-containing proteins are decreased in various types of cancer, and exert tumor-suppressive functions. (12)(13)(14)(15) MARVELD1 is a novel member of this family, with very limited work performed so far about its molecular function.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several MARVEL (proteins of the myelin and lymphocytes [MAL] and related proteins for vesicle trafficking and membrane link) domain-containing proteins have attracted increasing interest because they exhibit tumor suppressor activities and are frequently decreased via promoter methylation in breast, cervical, prostate, hepatocellular, esophageal and gastric carcinoma or cell lines. (12)(13)(14)(15) MARVELD1 is a member of MARVEL domain-containing proteins, located on human chromosome 10q24, a locus associate with multiple cancers. Our previous study shows that MARVELD1 is frequently downregulated in multiple cancers.…”
mentioning
confidence: 99%
“…Biomarkers can be used to predict prognosis and optimise therapeutic strategies. Hypermethylation of the MAL promoter has been shown in colorectal and oesophageal cancers and MAL has been proposed as a putative tumour suppressor in these cancer types (Mimori et al, 2003;Kazemi-Noureini et al, 2004;Mori et al, 2006). Moreover, it has been proposed as a candidate marker for early detection of these cancers, as methylation of MAL could already be detected in precursor lesions (Lind et al, 2007(Lind et al, , 2008Mimori et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In other gastrointestinal cancers, that is, colorectal and oesophageal cancer, the T-lymphocyte maturation associated protein MAL, involved in glycolipid-enriched membrane-mediated apical transport, has been described to be inactivated by promoter hypermethylation (Puertollano and Alonso, 1999;Mimori et al, 2003;Kazemi-Noureini et al, 2004;Mori et al, 2006;Lind et al, 2007). Promoter hypermethylation of MAL was a frequent event in these two cancer types, but infrequent in normal mucosa.…”
mentioning
confidence: 99%
“…Recently, downregulation of MAL has been associated with a variety of human epithelial malignancies. For example, Mimori et al (7) initially found that MAL was highly expressed in normal esophageal epithelia, but silenced in esophageal tumors. Later, inactivation of MAL was shown to be a common event in breast, head and neck, and gastric cancer (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%